2015
DOI: 10.1371/journal.pone.0136676
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insulin Resistance, Arterial Stiffness and Telomere Length in Adults Free of Cardiovascular Diseases

Abstract: BackgroundChronic inflammation and oxidative stress might be considered the key mechanisms of aging. Insulin resistance (IR) is a phenomenon related to inflammatory and oxidative stress. We tested the hypothesis that IR may be associated with cellular senescence, as measured by leukocyte telomere length (LTL), and arterial stiffness (core feature of arterial aging), as measured by carotid-femoral pulse wave velocity (c-f PWV).MethodsThe study group included 303 subjects, mean age 51.8 ±13.3 years, free of know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…The significantly shorter LTL measured in T2DM patients compared with healthy subjects over a wide age range has lent support to the hypothesis, which is also consistent with the beta cell failure and the increased senescence of vascular endothelial and smooth muscle cells seen in hyperglycemic media [49]. The notion is further reinforced by the inverse age-dependent relationship documented between LTL and insulin resistance [50]. Notably, in vivo evidence of increased senescence in both atherosclerotic plaques and renal tissue of diabetes patients suggest the relevance of this phenomenon to the vascular complications of diabetes [20, 50].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The significantly shorter LTL measured in T2DM patients compared with healthy subjects over a wide age range has lent support to the hypothesis, which is also consistent with the beta cell failure and the increased senescence of vascular endothelial and smooth muscle cells seen in hyperglycemic media [49]. The notion is further reinforced by the inverse age-dependent relationship documented between LTL and insulin resistance [50]. Notably, in vivo evidence of increased senescence in both atherosclerotic plaques and renal tissue of diabetes patients suggest the relevance of this phenomenon to the vascular complications of diabetes [20, 50].…”
Section: Discussionmentioning
confidence: 55%
“…The notion is further reinforced by the inverse age-dependent relationship documented between LTL and insulin resistance [50]. Notably, in vivo evidence of increased senescence in both atherosclerotic plaques and renal tissue of diabetes patients suggest the relevance of this phenomenon to the vascular complications of diabetes [20, 50]. Increased beta cell senescence in diabetic patients has also been demonstrated [51].…”
Section: Discussionmentioning
confidence: 99%
“…Ba-PWV was independently and positively associated with fasting plasma glucose, with one-hour post-challenge glucose or with HOMA-IR index in general population, in the pre-diabetic subjects, and in non-diabetic hypertensive subjects [ 105 , 106 , 107 , 108 , 109 ]. Finally, a recent study in middle-aged subjects free of CVD demonstrated the relationships of Cf-PWV with HOMA-IR index (direct) and telomere length (inverse), and suggested that insulin resistance linked with chronic inflammation can enhance telomere shortening (a marker of cellular senescence), and thus induce accelerated vascular aging [ 110 ].…”
Section: Arterial Stiffnessmentioning
confidence: 99%
“…Lifestyle factors known to modulate aging and age-related diseases might also affect telomerase activity. Obesity [ 42 ], insulin resistance [ 43 , 44 ], and cardio-vascular disease processes [ 45 , 46 ], which are related to oxidative stress and inflammation, have all been linked to shorter telomeres. Smoking, exposure to pollution, lower physical activity, psychological stress, and unhealthy diet significantly increase the oxidative burden and the rate of telomere shortening [ 47 - 53 ].…”
mentioning
confidence: 99%